2018
DOI: 10.3897/mycokeys.39.27014
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostomatoid fungi associated with pines infected by Bursaphelenchus xylophilus and Monochamus alternatus in China, including three new species

Abstract: The activity of the pine wood nematode Bursaphelenchusxylophilus leads to extremely serious economic, ecological and social losses in East Asia. The nematode causes pine wilt disease, which is currently regarded as the most important forest disease in China. The pathogenic nematode feeds on dendrocola fungi to complete its cycle of infection. As the vector of the nematode, the Japanese pine sawyer (Monochamusalternatus) also carries dendrocola fungi. Pine woods, infected by B.xylophilus and tunnelled by M.alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 71 publications
4
25
0
Order By: Relevance
“…Ophiostoma lotiforme resided in a species complex previously reported as group A (Chang et al 2017), together with O. saponiodorum, O. pallidulum, O. acarorum, and O. massoniana (Linnakoski et al 2010, Wang et al 2018. In our study, O. lotiforme was isolated from a single location (Inner Mongolia) from Pinus sylvestris var.…”
Section: Discussionsupporting
confidence: 56%
“…Ophiostoma lotiforme resided in a species complex previously reported as group A (Chang et al 2017), together with O. saponiodorum, O. pallidulum, O. acarorum, and O. massoniana (Linnakoski et al 2010, Wang et al 2018. In our study, O. lotiforme was isolated from a single location (Inner Mongolia) from Pinus sylvestris var.…”
Section: Discussionsupporting
confidence: 56%
“…In recent years, 98 ophiostomatoid species, including 49 new species, have been reported in association with bark beetles from China (Table S1 ) (Lu et al 2009a , 2009b ; Paciura et al 2010a , 2010b ; Zhou et al 2011 , 2013 ; Taerum et al 2013 ; Yin et al 2015 , 2016 , 2019 , 2020 ; Wang et al 2016 , 2018 , 2019 , 2020 ; Chang et al 2017 , 2019 ; Liu et al 2017 ). The study by Chang et al ( 2017 ) was the first to report ophiostomatoid fungi associated with phoretic mites.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we recovered seven species of ophiostomatoid fungi including four previously undescribed species from the Shandong province of China. The previous study from this province, reported two new ophiostomatoid fungi associated with B. xylophilus and M. alternatus collected from two pine species (Wang et al, 2018). Thus far, more than 10 bark beetle species have been reported from this province (Bai, 1985;Zhu et al, 1991).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, an ophiostomatoid fungus can symbiotically associate with multiple beetle species. Recently, six ophiostomatoid fungi were isolated from M. alternatus in China (Zhao et al, 2014;Wang et al, 2018). Among them, Ophiostoma ips were previously isolated from B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation